Rancang Bangun Prototipe Pengoptimal Charging Baterai pada Mobil Listrik dari Pembangkit Tenaga Surya dengan Menggunakan Sistem Boost Converter - Gurum Ahmad Pauzi; Diana Rahma; Sri Wahyu Suciyati; Arif Surtono (Journal of Energy, Material, and Instrumentation Technology, 2020)
In this research, the lithium-ion 48 Volt battery charging system's design was carried out on the prototype electric car using the boost converter tool. Boost converter consists of several circuit systems, namely oscillator circuit, trigger circuit, switching circuit, inductor, and DC output. IC TL 494 as pulse and frequency wave generator, used to regulate the switching process on the MOSFET circuit in the boost converter. This research was conducted by presenting variations in the inductor wire's diameter to determine the result of the current output used for the filling process by varying the diameter by 0.8 mm, 4 mm, and 8 mm. The number of wire twists used remains 5:27 and produces an output voltage boost converter of 54 Volts. The results showed the inductor wire's diameter affected the output of the boost converter and the length of battery charging time on the electric car. The length of time of battery draining at the wire's diameter is 0.8 mm, which is for 680 minutes, at the wire 4 mm diameter for 290 minutes, and at the diameter of the wire, 8 mm is for 400 minutes. The boost converter has the advantage of being more efficient in terms of dimensions, resulting in 3 times the voltage and power increase compared to the input voltage. The maximum panel input power of 14.5 Watts when added boost converter maximum power increased by 47.84 Watts.